Analisis Kebakaran Hutan Dan Lahan Di Provinsi Riau - Ardhi Yusuf; Hapsoh Hapsoh; Sofyan Husein Siregar; Dodik Ridho Nurrochmat (Dinamika Lingkungan Indonesia, 2019)
Riau is one of the provinces in Indonesia that often experience forest and land fires. Forest and land fires cause enormous environmental, economic, and social losses and damages that even cause disruption of political relationship between countries. This study aims to determine the relationship between biophysical, socioeconomic, and policy factors in influencing the occurrence of forest and land fires in Riau Province Based on researh, it is known that there is a correlation between forest and land fires variables in Riau Province to distance from 15 variables, ie peatland, river, road, forest cover, plantation cover, plantation, settlement (built up area), dry land, Timber Forest Product Utilization License, plantation concession, other use areas, protected forest areas, production forests, conversion production forest and limited production forest.